PHASE TRANSITION AND STRUCTURAL FEATURES OF CRYSTALS IN BINARY KALSI3O8-KFESI3O8 SYSTEM AT P = 100 MPA AND T = 400-600°C - Taroev V.K.; Kashaev A.A.; Lashkevich V.V.; Goettlicher J.; Pentinghaus H.; Wulf-Bernotat X.; Tauson V.L.; Suvorova L.F.; Kroll H. (My University, 2003)
The phenomenon of the iron incorporation into feldspars because of wide abundance is of particular interest for investigators in order to get the information about the conditions of formation and structural features of Fe-containing feldspars. From literature data, it is known [1] that there are some limitations of the iron incorporation into feldspar which, together with an extremely slow structural transformation after crystallization and the absence of quenching, are the main reasons for ambiguous interpretation of P-T-x conditions of origin of feldspar-containing rocks. The most essential limitation for natural conditions is low oxygen fugacity, which is close to buffer association Ni-NiO of QFM. The goal of our investigation is to experimentally study phase relations and estimate the structural state of solid solutions in the system KAlSi3O8-KFeSi3O8 depending on hydrothermal conditions.